Choice and auction design in the allocation of food to food banks - Altmann, SM (2024)
Feeding America, an organisation responsible for feeding 130,000 Americans every day, distributes donated food among a network of participating food banks. Feed- ing America’s allocation mechanism, the ‘Choice System’, uses repeated rounds of simultaneous first-price auctions to allow food banks to signal which types of food they need from Feeding America. This provides food banks a large degree of choice over the types of food they receive. This thesis examines the welfare and distribu- tional consequences of enabling this choice.